(untitled) (CIPEEX, 2022)
INTRODUCTION: BECAUSE OF THE HIGH PREVALENCE AND MORTALITY RATES OF CERVICAL CANCER (UCC), THE MAINSCREENING STRATEGY IS THE PAP TEST. IN SPITE OF THE CONSTANT EFFORTS IN THE EDUCATION OF THE POPULATION THEADHESION OF THE EXAMINATION IS BELOW THE RECOMMENDED ONE. THE NURSE HAS A FUNDAMENTAL ROLE IN THE WHOLEPROCESS OF PREVENTION AND HEALTH PROMOTION OF THIS DISEASE, RETURNING TO AN ASSISTANCE IN AN INTEGRATED ANDHUMANIZED WAY IN THE PROCEDURE OF COLLECTING THE CYTOPATHOLOGICAL EXAMINATION. OBJECTIVE: TO IDENTIFYNURSING CARE IN THE PREVENTION OF CCU IN LITERATURE REVIEW. METHOD: INTEGRATIVE LITERATURE REVIEW OF ARTICLESPUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LATIN AMERICAN ANDCARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND NURSINGDATABASE (BDENF), IN THE PERIOD BETWEEN 2012-2018, IN THE PORTUGUESE LANGUAGE. FOR THE ANALYSIS OF THEDATA THE RECOMMENDATIONS OF MENDES ET AL. (2008), WHICH PROPOSES SIX STEPS FOR THE ELABORATION OF A GOOD,EFFECTIVE, PRECISE AND RELEVANT INTEGRATIVE REVIEW. RESULTS: WE INCLUDED 14 ARTICLES IN THIS REVIEW. TWOCATEGORIES EMERGED: THE COP X THE DIFFICULTIES OF NURSING TO CARRY OUT THE PREVENTION OF CCU AND THE NURSE’SROLE IN THE PREVENTION OF CCU. THE LACK OF KNOWLEDGE AMONG THE FEMALE POPULATION DETERMINES THE DIFFICULTIESIN PERFORMING THE COP EXAM. WOMEN FEEL EMBARRASSED ABOUT EXPOSING THEIR GENITAL ORGANS AND HAVING THEMMANIPULATED BY A HEALTH PROFESSIONAL, THUS CAUSING DIFFICULTIES FOR THE PATIENT, BECAUSE THE PATIENT CAN NOT RELAXAND THEN HAVE A MORE PAINFUL EXAMINATION THAN THE COMMON ONE. SOME STUDIES HAVE SHOWN THAT THEGYNECOLOGICAL POSITION CAUSES A FEELING OF IMPOTENCE, OR LOSS OF THE BODY’S OWN DOMAIN, CAUSING FEAR DURINGTHE TEST. THOSE WHO ARE MARRIED FEEL IMMUNE TO SEXUALLY TRANSMITTED DISEASES, AND ANOTHER PARTY SAYS THAT THETEST IS NOT PERFORMED BECAUSE OF A LACK OF SYMPTOMS OR EMBARRASSMENT TO BE EXPOSED DURING THE COLLECTION.AND THE LACK OF KNOWLEDGE ON THE PART OF THESE WOMEN REGARDING THE NURSE’S ABILITY TO PERFORM THE POPCOLLECTION SHOWS THAT THE NURSE PROFESSIONAL IS RESPONSIBLE FOR THE PRACTICE OF COLLECTING THE EXAM, PREFERRINGTHE MEDICAL PROFESSIONAL. THE NURSING CONSULTATION IS AN ACTION FOR PREVENTION, WHICH CONSISTS OF DATACOLLECTION, PHYSICAL EXAMINATION, CARE PLANNING, NURSING DIAGNOSES AND PRESCRIPTION. IN THIS WAY, THEPROFESSIONAL SHOULD RETURN TO ASSISTANCE FOR TEACHING SELF-CARE. FINAILS CONSIDERATIONS: CERVICAL CANCERIS NOW THE FOURTH CANCER THAT KILLS THE MOST IN BRAZIL THEREFORE, IT IS EXTREMELY IMPORTANT TO PREVENT AND DIAGNOSEEARLY, THIS IS A ROLE FOR NURSES, TO DO IT SUCCESSFULLY SO THAT THERE IS A REDUCTION OF MORTALITY IN THE COUNTRY. TODAYWE CAN OBSERVE THAT THE LACK OF INFORMATION REGARDING THE REFERRED CANCER IS STILL VERY HIGH, SO IT IS ALSO THE ROLEOF NURSING TO ORGANIZE HEALTH EDUCATION IN A WAY THAT CAN RESOLVE TIMELY DOUBTS AND TABOOS THAT PREVENTPREVENTION.